Intention to Invest has a High Impact on Decision Making? New Contribution to the Planning Field of Financial Behavior in Indonesia - Yu. Yuliani; T. Taufik; Sh. Malinda (Финансы: теория и практика, 2024)
The study’s purpose is to determine empirical evidence on the effect of financial attitude, knowledge, and perceived risk on intention to invest, reinvestment, level of trust in the platform, and investment satisfaction. The data were collected via an Online Google form from May to July 2022, through a survey of 401 respondents from cities in Indonesia, and were analyzed by structural equation modeling with partial least squares. The results showed that financial attitude has a significant positive effect on the intention to invest and knowledge, while it is insignificant on perceived risk. The intention to invest has a high impact on decision-making. Reinvestment is significantly influenced by intention, decision-making, and trust. The effect of trust has a high impact on reinvestment, which has a significant positive influence on financial satisfaction. This study has made a new contribution to the planning field of financial behavior, regarding investment decisions in terms of monetary assets for unit analysis. However, in further study for businesses or SMEs with unique characteristics, some adjustments are needed in the aspects of testing and model improvement to increase applicability.